Pengelolaan Terapi pada Pasien dengan Ulkus Diabetes Berkaitan dengan Gangguan Pembuluh Darah Perifer (Literature Review) - Titin Supriatin; Primadana Rizki; Hilda Anggraeni; Nisa Adyaningsih; Cinta Arifah; Hani Tri Hidayani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Peripheral vascular disorders (PVD) are common in patients with diabetes mellitus (DM) due to chronic metabolic disorders involving carbohydrates, fats and proteins due to insulin deficiency. PVD can lead to serious complications, such as diabetic ulcers, which increase the risk of limb amputation by 15-30% and mortality rate by 17-32% in Indonesia. Effective therapeutic management is crucial to reduce the risk of amputation by 50-75% and accelerate wound healing. The multidisciplinary approach in diabetic ulcer therapy includes antibiotics, hyperbaric oxygen therapy (TOHB), Burger Allen Exercise (BAE), honey therapy, hypnosis therapy, acupuncture - acupressure therapy, and Adjuvant Extracorporal Shockwave (AES), as well as low laser therapy. This combination of interventions provides a synergistic effect in supporting wound healing and improving patients' quality of life. This literature review aims to assess therapeutic management interventions in diabetic ulcer patients, by analyzing 89 articles from Google Scholar (period 2017-2024), of which 74 articles were excluded and 15 articles met the inclusion criteria. Keywords used included diabetes mellitus AND peripheral vascular disorders. The results of the review showed that an evidence-based approach and multidisciplinary collaboration are essential for the successful management of diabetic ulcers, supporting the healing process and improving patients' quality of life.